Short Communication: The population number of Pelung chickens in West Java, Indonesia - Indrawati Yudha Asmara; Dani Garnida; Heni Indrijani (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Asmara IY, Garnida D, Indrijani H. 2022. Short Communication: The population number of Pelung chickens in West Java, Indonesia. Biodiversitas 23: 3373-3378. Domestic farm animals or, Animal Genetic Resources (AnGR), are part of the global biodiversity. The existence of AnGR, mainly local breeds, is threatened, and their population data is still far from complete. This study provides information about Pelung chickens (Gallus gallus domesticus), a local chicken breed in Indonesia. The purpose of this study was to offer an overview of the population, effective population size, and inbreeding rate of Pelung chickens in four regencies in West Java, Indonesia. The method used in this study was a survey of fanciers and breeders of Pelung. Interviews were conducted to reveal the production system and population data. The data were analyzed descriptively and then calculated to estimate the effective population size (Ne) as well as the rate of inbreeding (?F). This preliminary survey indicated that there was a change in the distribution of the Pelung chicken, in which Garut Regency has the largest population number of Pelung, with 5664 birds of all ages. In this study, Pelung chickens in different areas had high Ne (267-569), and the ?F can be considered fairly low (0.09-0.19). The results of the study are probably the first documentation of the population number of Pelung chickens in at least ten years. This research is the initial study that forms the basis for conducting a comprehensive survey on the Pelung chicken. This study offers an upper limit result of Ne, so that accurate diversity parameter such as using genomic information is required.